2022
DOI: 10.1111/jbi.14329
|View full text |Cite
|
Sign up to set email alerts
|

Changes in β‐diversity of saproxylic beetles along environmental gradients in temperate forests depend on species relative abundances

Abstract: Aim: Understanding the processes that structure biological communities along environmental gradients remains one of the main aims of ecological research. A leading question is how differences in species composition between sites, that is, β-diversity, change in habitats ordered along environmental gradients and how such changes vary with species relative abundances. The existing literature remains descriptive, mostly comparing communities from different parts of a gradient, but not tracking sequential changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…For example, rare species may be more spatially restricted and have higher habitat specialization, so are much more vulnerable to environmental changes than common species (Benone et al., 2022 ). Furthermore, previous studies have found that dominant, common, and rare species can contribute different weights to the variation of beta diversity (Sebek et al., 2022 ) and altering species relative abundances and/or changes to the size of species pool can also influence local diversity variation (Blowes et al., 2022 ). Hence, these findings highlight the need for further research on the relative roles of common and rare species to biodiversity patterns in order to provide deeper insights into underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rare species may be more spatially restricted and have higher habitat specialization, so are much more vulnerable to environmental changes than common species (Benone et al., 2022 ). Furthermore, previous studies have found that dominant, common, and rare species can contribute different weights to the variation of beta diversity (Sebek et al., 2022 ) and altering species relative abundances and/or changes to the size of species pool can also influence local diversity variation (Blowes et al., 2022 ). Hence, these findings highlight the need for further research on the relative roles of common and rare species to biodiversity patterns in order to provide deeper insights into underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the relationship of beta diversity in different facets and different spatial or environmental scales (even less concerned) can help us understand the maintenance processes of biodiversity (Meynard et al., 2011 ). Additionally, increasing studies have found that differences in species relative abundance (i.e., common or rare species) or species evenness could also put importance on the stochastic and deterministic processes of beta diversity, which was another important component of diversity (Li et al., 2019 ; Sebek et al., 2022 ; Wilsey & Potvin, 2000 ). Furthermore, effective conservation strategies require comprehensive knowledge considering multiple facets of biodiversity, including alpha/beta components of species richness, taxonomic and functional diversity, and their relationships (Kang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, diverse native communities with fuller niche partitioning and lower resource availability may have limited exotic establishment and propagule production. Some studies show that beta diversity correlates with species rarity, which may be caused by the poor reproductive performance of rare species (Hubbell, 1979; Sebek et al, 2022). Exotic plants often occur at multiple sites via high propagule pressure, which can lead to increased community similarity, especially during early establishment (Kempel et al, 2013; Muthukrishnan & Larkin, 2020).…”
Section: Discussionmentioning
confidence: 99%